(untitled) (Agricultural Engineering, 2020)
Field tests on the quality of shaking off redcurrant fruit Rosetta cultivar with a half-row trailer harvester “Marek” produced by Dom-Wid were carried out. The tests were performed at two average working speeds ῡ1 = 0.47 m·s−1; ῡ2 = 0.60 m·s−1 and two rotational speeds of a tractor n1 = 1500 rpm; n2 = 1900 rpm. The length and diameter of shoots of redcurrant, length of a bunch, number of fruits in a bunch and mass of fruit were measured. Weather conditions were presented: rain fall, air temperature and moisture. Analysis of results showed that the working speed and the rotational speed has a significant impact on the quality and amount of the yield. At the highest rotations, the harvesting quality of fruit by a harvester was the worst and was 77.15%.